To study the efficacy of ropivacaine (0.75%) with or without butorphanol as an adjuvant in single shot epidural anaesthesia in lower limb orthopedic surgeries (International Journal of Biomedical Research, 2014)
Objectives: To evaluate the efficacy of Butorphanol as an adjuvant to Ropivacaine (0.75%) Plain in Single Shot Epidural Anaesthesia on: Onset of Sensory and Motor Block; Duration of Sensory and Motor Block.; The Hemodynamic Changes Intra operatively and Post operatively; Duration of post-operative analgesia, Side Effects / Complications if any. Material and Methods: 60 adult patients of ASA I/II, posted for elective lower limb surgeries in orthopaedics were divided in to two groups randomly. Group R (n = 30) were given a single shot dose of epidural Ropivacaine 0.75% 20ml and Normal Saline equivalent to 15gm/kg of Butorphanol. Group B (n = 30) were given a single shot dose of epidural Ropivacaine 0.75% 20ml with 15ug/kg Butorphanol as an adjuvant.. Results: The mean onset time to achieve desired sensory block was rapid in the Group-B compared to Group-R. The mean time to achieve motor block was faster in Group-B compared to Group-R. The hemodynamic parameters were comparable at all the time among both the groups. Total duration of analgesia was significantly prolonged in Group-B compared to Group-R. No major side effects were observed in either of the group. Conclusion: Epidural 0.75% Ropivacaine with Butorphanol showed better clinical profile as compared to 0.75% Ropivacaine plain for lower limb orthopedic surgeries in single shot epidural anaesthesia.